Pulmonary bioaccessibility of trace metals in PM2.5 from different megacities simulated by lung fluid extraction and DGT method. (March 2019) - Luo, Xiaosan; Zhao, Zhen; Xie, Jiawen; Luo, Jun; Chen, Yan; Li, Hongbo; Jin, Ling
Abstract: Atmospheric fine particulate matters (PM2.5 ) pose significant risks to human health through inhalation, especially in the rapidly developing China due to air pollution. The harmful effects of PM2.5 are determined not only by its concentrations and hazardous components from diverse sources, but more by their bioavailable fractions actually absorbed by human body. To accurately estimate the inhalation risks of airborne metals, a physiologically based bioaccessibility method combining Simulated Lung Fluid (SLF) extraction and Diffusive Gradients in Thin-films (DGT) approaches was developed, representing the dissolution of particulate metals into lung fluid and the subsequent lung absorption of free metal cations in solution, respectively. The new method was used to compare the lung bioaccessibility of typical trace metals in PM2.5 from three China megacities (Shanghai and Nanjing in the east, Guangzhou in south) during heavy pollution seasons. Generally, the SLF bioaccessibility (%) simulating the solubility of particulate metals in alveolar lung fluid was in order of Ni > Cd > Mn » Pb, while the succeeding DGT bioaccessibility representing labile metal fractions in solution phase absorbed directly by lung was lower and ranked as Ni ∼ Mn > Cd » Pb, thus Ni and Cd posed relatively higher potential risks owing to their high air pollution level and higher pulmonary bioaccessibility. Due to varied particle sources such as coal combustion and traffic emissions, some airborne metal concentrations (Pb, Ni) showed inconsistent spatial patterns with bulk PM2.5 concentrations, and also varied bioaccessibility in different regions. The framework for PM2.5 pollution risk assessments should be refined by considering both aerosol components and associated pollutants' bioaccessibility. Graphical abstract: Image 1 Highlights: Different airborne metals show varied pulmonary bioaccessibility. Airborne metal bioaccessibility varied with sources. Lung fluid extraction simulates solubility of particulate metals. DGT evaluates labile metals in solution efficiently absorbed by lung. Aerosol risks should consider components and human bioaccessibility.